2009
DOI: 10.1111/j.1399-6576.2009.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome, timing and adverse events in therapeutic hypothermia after out‐of‐hospital cardiac arrest

Abstract: Background: Therapeutic hypothermia (TH) after cardiac arrest protects from neurological sequels and death and is recommended in guidelines. The Hypothermia Registry was founded to the monitor outcome, performance and complications of TH. Methods: Data on out-of-hospital cardiac arrest (OHCA) patients admitted to intensive care for TH were registered. Hospital survival and long-term outcome (6-12 months) were documented using the Cerebral Performance Category (CPC) scale, CPC 1-2 representing a good outcome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
253
4
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 419 publications
(299 citation statements)
references
References 50 publications
24
253
4
5
Order By: Relevance
“…How could TH have a neutral effect on prognosis in these patients with non-shockable CA? By altering the risk/benefit ratio of this intervention, an increased incidence of TH-related side effects could be an explanation, although not firmly established [7,13,14]. In the present study, pneumonia was more frequent in the TH-treated patients-confirming previous data [14,15]but this was not related to CA rhythm.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…How could TH have a neutral effect on prognosis in these patients with non-shockable CA? By altering the risk/benefit ratio of this intervention, an increased incidence of TH-related side effects could be an explanation, although not firmly established [7,13,14]. In the present study, pneumonia was more frequent in the TH-treated patients-confirming previous data [14,15]but this was not related to CA rhythm.…”
supporting
confidence: 80%
“…Following at least three large indisputable RCTs and five concordant meta-analyses, TH is now recommended in the treatment of neonatal hypoxic-ischaemic encephalopathy because of its beneficial effect on survival and neurological disability [2,6]. Since 20-25 % of patients with non-shockable CA could finally survive with a favourable neurological outcome at hospital discharge and in the long term [7], it would be interesting to provide TH as the only available treatment to date able to minimize brain damage and long-term disability. Despite these arguments, nearly all studies including patients with non-shockable CA have shown no effect of TH or a modest benefit in favour of cooling.…”
mentioning
confidence: 99%
“…Es ist anerkannt, das Patienten nach einem Kreislaufstillstand mit ST-Hebungs-Infarktzeichen (STEMI) schnellstmöglich eine Koronarangiographie und eine PCI erhalten sollen. Da jedoch sowohl Thoraxschmerz als auch ST-Veränderungen bei den Patienten nach Kreislaufstillstand nur eingeschränkt korrekt einen akuten koronaren Verschluss voraussagen [660], soll bei allen Patienten nach Kreislaufstillstand, bei denen eine KHK angenommen werden kann, eine PCI in Erwägung gezogen werden [630,634,660,661,662,663,664,665,666]. Mehrere Studien weisen darauf hin, dass bei einem Patienten mit einem Kreislaufstillstand, der aufgrund eines ACS aufgetreten ist, die Kombination von Hypothermie und PCI machbar sowie sicher ist [630,634,639,666,667].…”
Section: Herz-kreislauf-systemunclassified
“…Otherwise, in regular regime, a dominant pacemaker spontaneously activates the tissue (propagation of plane waves of action potential). The generation of spiral waves in this model induced by hypothermia, corresponds to clinical studies shown that in case of cardiac arrest, the therapeutic hypothermia could provoke arrhythmia cardiac [18,19,20,21].…”
Section: Relevance Of Spiral Waves To the Arrhythmogenicitymentioning
confidence: 99%
“…However, other studies did show that cardiac arrhythmia occurs after HT. According to studies, the cardiac arrhythmia represents 6% ( [18]) to 7% − 14% [19], even reaches or 33% − 36% [20,21] of the total adverse events. So it is important to understand how the post-hypothermia-arrhythmia raises.…”
Section: Introductionmentioning
confidence: 99%